The Potential of Integrating Islamic Microfinance Institutions (BMT) with the Halal Tourism Ecosystem in Empowering the Local Creative Economy - Dimyati Dimyati (LPPM STIES BABUSSALAM, 2026)
The development of the halal tourism industry in Indonesia offers significant opportunities for regional economic growth through strengthening the creative economy-based micro, small, and medium enterprises (MSMEs). However, limited access to Islamic financing, low business capacity, and weak stakeholder integration remain obstacles to optimizing the economic benefits of halal tourism for local communities. This study aims to analyze the potential integration of Islamic Microfinance Institutions, specifically Baitul Maal wat Tamwil (BMT), with the halal tourism ecosystem to support the empowerment of the local creative economy. The study employed a qualitative approach with library research methods through analysis of various scientific literature, policy reports, regulations, and relevant previous research findings. Data were analyzed using content analysis techniques to identify the relationship between the Islamic financial intermediation function of BMTs and the development needs of the halal tourism ecosystem. The research results show that BMT has strategic potential as an intermediary institution that not only provides sharia-based financing, but also plays a role in business mentoring, sharia financial literacy education, strengthening halal business networks, and optimizing Islamic social funds such as zakat, infaq, sedekah, and productive waqf. The integration of BMT with the halal tourism ecosystem can increase the capacity of local creative economy actors through halal MSME financing, local wisdom-based product development, halal certification, marketing digitalization, and collaboration with local governments, tourism industry players, and community groups. This synergy contributes to increasing the competitiveness of halal tourism destinations, creating jobs, increasing community income, and strengthening a sustainable inclusive economy in accordance with the principles of maqashid sharia. This research implies that strengthening multi-stakeholder collaboration between BMT, the government, tourism industry players, halal certification institutions, and creative economy communities is an important strategy in building a competitive halal tourism ecosystem that is able to drive sustainable local economic growth